The Influence of Teacher Competence and Cooperation Climate on the Quality of Learning at Padang Panjang State High School - Netti, Surya; Susanto, Perengki (Economic Education and Entrepreneurship Journal, 2024)
This research aims to determine and analyze the influence of teacher competence and collaborative climate on the quality of learning in Padang Panjang State High School. The sample was 66 State High School teachers in Padang Panjang. This research uses a saturated sampling technique. This type of research is quantitative research. Data collection techniques use a questionnaire with a Likert scale model with 5 alternative answers. multiple linear regression analysis technique. The results showed that Teacher competency has a significant influence on the quality of learning at Padang Panjang State High School. Furthermore The climate of teacher collaboration has a significant influence on the quality of learning at Padang Panjang State High School. And Teacher Competency and Teacher Collaboration Climate have a significant influence on the quality of learning at Padang Panjang State High School.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.145-153